Faktor-faktor Iklan yang Dapat Menarik Penonton Untuk Menonton Iklan Skip-Ads di Youtube Sampai Selesai - Anita Chrishanti Puteri Tito; Claudy Gabriella (Jurnal Akuntansi)
Along with the changing times, technology plays an important role in the marketing world. The increasing use of the internet has led to the shift of marketing using print media into online media. Deployment of marketing strategies can be found through various platforms such as websites and social media. One popular website is used as a means to market your product or service is YouTube. If someone is using YouTube certainly will often encounter many types of ads, but the most common and often comes up is true view in-stream ads that are usually will appear before the video starts. The ad will run for 5 seconds before it was finally has available options for in-skip.